2020
DOI: 10.1017/s0033291720002950
|View full text |Cite
|
Sign up to set email alerts
|

White matter fiber microstructure is associated with prior hospitalizations rather than acute symptomatology in major depressive disorder

Abstract: Background Eighty percent of all patients suffering from major depressive disorder (MDD) relapse at least once in their lifetime. Thus, understanding the neurobiological underpinnings of the course of MDD is of utmost importance. A detrimental course of illness in MDD was most consistently associated with superior longitudinal fasciculus (SLF) fiber integrity. As similar associations were, however, found between SLF fiber integrity and acute symptomatology, this study attempts to disentangle associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…We speculate that it may be due to the higher HAMD scores, the longer duration of illness and the mixed recurrent patients of MDD in Zeng’s study. Previous study has concluded that lower FA values in the SLF were related with more hospitalizations and that SLF fiber integrity may reflect the cumulative disease burden in MDD ( 66 ). It also suggested that the damage in WM structures did not occur in the early stage of the disease, but emerged as the disease progresses further.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that it may be due to the higher HAMD scores, the longer duration of illness and the mixed recurrent patients of MDD in Zeng’s study. Previous study has concluded that lower FA values in the SLF were related with more hospitalizations and that SLF fiber integrity may reflect the cumulative disease burden in MDD ( 66 ). It also suggested that the damage in WM structures did not occur in the early stage of the disease, but emerged as the disease progresses further.…”
Section: Discussionmentioning
confidence: 99%
“…Especially association and commissural white matter fibers responsible for higher cognitive functioning, continue to develop throughout adolescence to early and middle adulthood [36,63]. This prolonged development is the underlying basis for white matter plasticity, which in turn would be necessary for environmental and (epi-) genetic factors to in turn influence fiber structure [63][64][65].…”
Section: Discussionmentioning
confidence: 99%